Meningkatkan Kepercayaan Diri Anak Terhadap Minat Belajar Dengan Pembelajaran Matematika di Panti Asuhan Eben Haezer - Friska Crhisti Hutauruk; Husni Thamrin (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
The community service program is a forum for implementing and carrying out the development of science and technology that is carried out outside the campus within certain time, work mechanisms and requirements. Community service carried out at the orphanage is a form of student service to provide useful knowledge for the surrounding community, especially at the orphanage. The author does community service at the Eben Haezer Orphanage which certainly has a special purpose to provide counseling in increasing interest in learning for the children of the Eben Haezer Orphanage. The main problem faced is the low interest in learning for the children at the orphanage, the low interest in learning and the learning environment where their achievement decreases at school and this is of course a problem for the children and at this orphanage. Learning interests of children/students can be influenced by learning objects, methods, learning strategies and approaches, teacher attitudes and behavior, learning media, learning facilities, learning environment and teacher's voice. From this interest in learning, it can lead to self-confidence that children have in the learning they want to achieve, especially in learning mathematics. The self-confidence that the child already has will become enthusiastic, as well as a high curiosity about new learning. Other activities that will be carried out include outreach, education, and motivation which will later change the mindset specifically for the children living at the Eben Haezer Orphanage so that they receive more knowledge not only in the school environment. Therefore, with the activities that will be carried out, the author intends to carry out a mini project at the orphanage using two tools in the assessment stage, the two tools are focus group discussion (FGD) tools and ecomap.